Penentuan Status Keberlanjutan Infrastruktur Perkotaan (Studi Kasus: Kota Bandarlampung) - Persada, Citra; Sitorus, Santun RP; Marimin, Marimin; Djakapermana, Ruchyat Deni (Jurnal Sosial Ekonomi Pekerjaan Umum, 2014)
The high increase of population in the cities has an implication on the higher needs of city infrastructure, however, in order to create availability of sustainable infrastructure is not easy. The city needs measurement tools to identify its ability in building sustainable infrastructure. The purpose of the writing of this paper is: (1) to formulate the criteria and indicators of city’s sustainable infrastructure development; (2) to assess the level or status of the city’s sustainable infrastructure; and (3) to identify influential factors in the development of city’s sustainable infrastructure. The criteria and indicators of sustainable infrastructure gained from literature studies and expert consultation through Focus Group Discussion (FGD) are 5 criteria and 47 indicators. Indicators for environment criteria cover the efficiency in the usage of resources and the minimization of wastes. Indicators for social criteria emphasize on the easiness in gaining basic services, security, comfort and the community participation. Indicators for economic criteria focus on the increase of society’s welfare and local economy development. Indicators for technology relate with the level of availabilty and infrastructure services. Indicators for good govermance criteria cover leadership, organizational capacity, infrastructure planning an law enforcement. The Multi-Dimensional Scalling (MDS) with Rapid Appraisal of Infrastructure (Rapinfra) analysis show that the sustainability status of Bandarlampung infrastructure is less sustainable with the score of 38,05%. Influential indicators are gained from leverage factor analysis result towards the score of sustainability index for 26 indicators, which consists of : 4 indicators for enviroment criteria, 6 indicator for social criteria, 3 indicators for economy criteria, 8 indicators for technology criteria and 5 indicators for good govermance.